Motivasi Petani dalam Meningkatkan Pendapatan Usaha Tani Padi Sawah di Kelurahan Baruga Kecamatan Baruga Kota Kendari - Sukmawati Abdullah; Awaluddin Hamzah; Jusnatang Jusnatang (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims to: 1) determine the level of motivation of farmers in Baruga Village, Baruga District, Kendari City. 2) find out the income level of rice farmers in Baruga Village, Baruga District, Kendari City. 3) find out the relationship between motivation and income of lowland rice farmers petani in Baruga Village, Baruga District, Kendari City. This research was conducted in Baruga Village, Baruga District, Kendari City in January 2021. With a sample of 24 people. This research is quantitative. Data were analyzed using class interval formulas and quantitative descriptive deskriptif using Spearman rank correlation to determine the relationship between motivation and income. The results of this study indicate that the level of motivation (direction and persistence) of rice farmers is high, while for motivation (direction) is classified as moderate. And the relationship between farmer motivation and income is said to have a close relationship. (significant).